Estimation of the Impact on Treatment Costs of a Switch to Nonacog Beta Pegol (N9-GP) for the Treatment of Adults with Hemophilia B in Canada Based on Real-World Factor IX (FIX) Consumption and Clinical Outcomes Pre- and Post-Switch - MacDonald, Vance; Lee, Xin Ying; Caillaud, Alexandre; Luckevich, Maria; Bentley, Anthony (Blood, 2020)
Introduction: Congenital hemophilia B is a rare blood disorder, caused by mutations in the F9 gene that lead to dysfunctional, reduced, or no clotting factor IX (FIX), resulting in prolonged bleeding episodes and in severe cases, spontaneous bleeding episodes. Maintaining sufficient FIX activity in the bloodstream through routine prophylactic administration of FIX, is the standard of care for prevention of bleeds in hemophilia B patients in Canada. Breakthrough bleeding (BTB) episodes are treated acutely with additional doses of FIX. In Canada, real-world data for patients with hemophilia B, including clinical outcomes and consumption rates of FIX, are recorded in the Canadian Bleeding Disorders Registry (CBDR). FIX products for patients with hemophilia B are subject to national competitive procurement processes administered by the Canadian Blood Service (CBS) and Héma-Québec. Nonacog beta pegol (N9-GP), an extended half-life (EHL) recombinant FIX concentrate, was recently awarded a CBS contract and subsequently made available across Canada (except Québec) from April 1, 2018 to adult patients. For those patients already on another EHL FIX treatment, a forced switch to N9-GP occurred. The objective of the present study was to estimate the impact on treatment costs of switching from a prior FIX to N9-GP, based on real-world annualized bleed rates (ABRs) and FIX consumption volumes (pre- and post-N9-GP switch) for patients on prophylaxis with their previous treatment and N9-GP, as recorded in the CBDR as of 30 September 2019. Methods: Real-world data from the CBDR for FIX consumption and ABR were used to inform a cost consequence model, developed in Microsoft Excel. Only patients for whom data existed in the CBDR for 6-months pre-switch to N9-GP and who had received ≥3 months of N9-GP treatment were included. Since April 2018, N9-GP replaced eftrenonacog alfa as the EHL product available to adult patients covered by CBS, while nonacog alfa continued to be the recombinant standard half-life (SHL) product available. Based on this, it was assumed that the EHL to N9-GP switches were from eftrenonacog alfa and the SHL switches are from nonacog alfa. For comparison of N9-GP with nonacog alfa and eftrenonacog alfa, treatment of adult males (assumed body weight of 70 kg) with severe hemophilia B was modeled over a 1-year time horizon. Since the competitive procurement process used in Canada results in confidential per-unit FIX prices, a price from a similar market was used for assessment of the cost impact. The German market was selected because all recombinant FIX products available in Canada are reimbursed in Germany. Converting the German per-IU prices, as published in the Lauer-Taxe®, using the Bank of Canada average exchange rate for the previous year, resulted in a price of CAD $2.54, $1.50 and $2.18 per IU for N9-GP, nonacog alfa, and eftrenonacog alfa, respectively. Real-world annualized mean FIX consumption volumes for prophylaxis, per BTB and real-world mean total ABRs for each product were then multiplied by the price per IU for each FIX product to derive estimates of real-world annual treatment costs associated with the use of nonacog alfa and eftrenonacog alfa (pre-switch), and N9-GP (post-switch). Results: Real-world annual prophylaxis consumption volumes, as reported in the CBDR, were reduced following treatment switch to N9-GP (Table 1). The switch to N9-GP was associated with improved ABRs, from 7.38 to 2.56 and 4.76 to 2.68 for patients on prior treatment with nonacog alfa and eftrenonacog alfa, respectively. Comparative treatment costs (for prophylaxis and BTB) based on real-world data were reduced from $643,400 to $412,700 when switching from nonacog alfa to N9-GP and from $486,938 to $358,822 when switching from eftrenonacog alfa to N9-GP. Treatment with N9-GP was therefore associated with a 35.8% and 26.3% reduction in costs following a switch from nonacog alfa, and eftrenonacog alfa, respectively. Conclusion: Real-world FIX consumption and bleeding outcomes data demonstrate that N9-GP is cost-saving compared with nonacog alfa and eftrenonacog alfa (assuming per-IU prices based on German costs converted to Canadian dollars) while also achieving a reduction in ABR, regardless of whether patients previously received an SHL or EHL FIX product. N9-GP can therefore be considered a dominant treatment option compared with nonacog alfa and eftrenonacog alfa for the treatment of hemophilia B. [Display omitted] MacDonald:Novo Nordisk Canada Inc: Current Employment. Lee:Novo Nordisk A/S: Current Employment. Caillaud:Novo Nordisk Canada Inc: Current Employment. Luckevich:Novo Nordisk Canada Inc.: Current Employment. Bentley:Mtech Access: Consultancy, Other: Consultant for Novo Nordisk.